Efeito do envelhecimento e do treinamento resistido sobre ossos de ratos - Bogni, Fabio Henrique (Universidade Federal de São Carlos, 2013)
The purpose of this study was to investigate the influence of high-intensity resistance training on the activity of bone matrix metalloproteinases (MMPs), biometric, biomechanical, biophysical and biochemical properties of young and aged rats. We used 62 intact male rats, Rattus norvegicus albinos ("Wistar") randomly distributed into 4 groups: young sedentary (YS), young trained (YT), older sedentary (OS) and old trained (OT). The rats (YT and OT) performed resistance training, during 12 weeks, consisted of climbing a vertical ladder with weights fixed on their tails. The sessions were executed three times a week, every other day. The biomechanical, physical, biochemical and MMP-2 activity of bones analysis were performed, respectively, using a universal testing machine, Archimedes principle, commercial kit and zymography. In this study, the training promoted a reduction of body mass in YT animals, and reduced bone stiffness and pro MMP activity in the OT group. With aging occured differences of the charge of loading (absolute and relative) between the trained groups (YT greater than OT), body mass (increased among youth, increased initial mass and decreased final mass in the elderly), an increase in the right femur length, mineral material (calcium and phosphorus) and stiffness, however, a decrease of organic material. In this study, the training protocol did not cause effects on bone tissue chosen for analysis. In this study, the training protocol did not cause effects on bone tissue chosen for analysis.
Keywords: Fisiologia; Treinamento resistido; Ratos idosos; Metaloproteinase (MMP-2); Biomecânica óssea; Biofísica óssea; Atividade de MMP-2; Propriedades biomecânicas; Resistance training; Aged rats; MMP-2 activity; Physical and biomechanical; Properties of bone; CIENCIAS BIOLOGICAS::FISIOLOGIA